Ekstrak daun meniran (Phyllanthus niruri. L) memperbaiki kerusakan sel-β pankreas dan menurunkan kadar gula darah tikus wistar hiperglikemia diinduksi aloksan - Sri Wahjuni (DiscoverSys Inc., 2017)
Increased production of reactive oxygen species (ROS) is probably one of cause the present of hyperglycemia. This study aims to investigate the effectiveness of Phyllanthusniruri L leaves extract to repair pancreatic b-cells and decrease of blood glucose levels on hyperglycemia wistar rat aloxan induced.This is a true experimental employing pre and posttest control group design. Experimental was started by generating hyperglycemia of the 32 rats using aloxan. Then, the rats were divided into two groups, i.e. control group (C) and treatment group (T). Treatment group was fed with 5,0 mg/Kg bw/d phyllanthus niruri L extract. Repaired of pancreatic b-cells for these two groups were compared descriptively using immunohysto-chemistry. In addition blood glucose levels between these two groups were compared statistically using t-test.The results indicate that there was a different between pancreatic b-cells in these two groups. In addition there were also a significant different between blood glucose levels in these two groups, i.e. for control group were 217.46±23.38 mg/dL (pretest) and 206.17±22.16 mg/dL (posttest) compared to 217.49±23.33 mg/dL (pretest) and 117.93±21.23 mg/dL (posttest) for treatment group. It can be concluded that Phyllanthusniruri L leaves extract in a dose of 5.0 mg/kg bw/d effective to repair pancreatic b-cells disability and also for decreasing blood glucose levels on hyperglycemic wistar rats. This is probably due to the antioxidant and anti inflammation activity of this leaf.